Personal Networking in Russian Post Soviet Life - Bulter, Bella; Purchase, S. (School of Management, Curtin University of Technology, Perth, Western Australia and the Singapore Human Resources Institute, 2004)
Liberalisation of the Russian economy potentially offers Western investors business engagement opportunities in an environment significantly different from Western culture. Knowledge of the institutional, managerial and contextual nuances, which include blat, is vital for the effective management of human resources, and thus, successful building of multinational enterprises. This paper gives an explanation of the meaning of blat, analyses the main features of blat as personal networking and provides some common examples of using blat. By analysing prerequisites of blat in the communist regime as well as in the conditions of the market economy, it is argued that despite the shift in the current use of blat it is ingrained in the Russian psyche, and consequently, has a strong impact on business relationships and management of human resources in Russia. Such accommodation of blat contributes into the understanding of the Russian unique set of norms and standards for doing business and practices of human resources management.